2021
DOI: 10.1016/j.psychres.2020.113604
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity and protracted symptoms after COVID-19

Abstract: Highlights We studied the psychiatric morbidity and the protracted symptoms in recently recovered COVID-19 patients We also looked at potential factors that might influence psychiatric morbidity Significant symptoms of posttraumatic stress, anxiety and depression were found PTSD symptom severity was the sole independent predictor of the presence of protracted symptoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
132
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 30 publications
(32 reference statements)
18
132
1
4
Order By: Relevance
“…All of these studies were conducted in Asia (three in China, one in Korea, and one in Vietnam). Just after treatment discharge of mild cases in Turkey, 18.4% and 18.8% were considered having ‘probable’ anxiety and depression ( Poyraz et al, 2021 ).The prevalence of a clinically significant depressive symptoms in our study (26.2%) is within range of previous studies, but clinically significant anxiety symptoms were greater (22.4%) than previously reported values (6.8–21.0%). Our results were more similar to those found by Zhang et al (2020) , who sampled home-quarantined COVID-19 patients.…”
Section: Discussionsupporting
confidence: 67%
“…All of these studies were conducted in Asia (three in China, one in Korea, and one in Vietnam). Just after treatment discharge of mild cases in Turkey, 18.4% and 18.8% were considered having ‘probable’ anxiety and depression ( Poyraz et al, 2021 ).The prevalence of a clinically significant depressive symptoms in our study (26.2%) is within range of previous studies, but clinically significant anxiety symptoms were greater (22.4%) than previously reported values (6.8–21.0%). Our results were more similar to those found by Zhang et al (2020) , who sampled home-quarantined COVID-19 patients.…”
Section: Discussionsupporting
confidence: 67%
“…Our prevalence rates are in the lower range of the 7–34%, which was reported in other cohorts of COVID-19 survivors following hospitalization at comparable time points [ 6 , 7 , 8 , 18 , 19 , 20 , 21 ], and much lower than the 96% reported during hospitalization in a study using the PCL-C, a civilian version of a PTSD questionnaire based on DSM-IV [ 22 ]. Two of the studies also comprised both hospitalized and non-hospitalized subjects [ 7 , 21 ].…”
Section: Discussioncontrasting
confidence: 62%
“…This finding suggests that although having a chronic illness predisposes patients with acromegaly and CD to be strongly affected by COVID-19, they do not experience the pandemic as more traumatic than the general population. As a matter of fact, in a study by Poyraz et al (2020), researchers evaluated the protracted psychiatric symptoms after COVID-19, and showed that the severity of PTSD symptoms did not change to the presence of a chronic medical disease [37]. Patients with PCR-confirmed COVID-19 had significantly higher rates (48%) of PTSD than the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Increased scale scores showed the presence of higher levels of anxiety. The scores for the STAI questionnaire ranged from 20 to 80 points and was split into four groups: no anxiety (0-20), mild (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), moderate (40-59), and severe anxiety (60-80). An abnormal STAI score was subject when the participants' score was ≥ 40.…”
Section: State-trait Anxiety Inventory (Stai S-t)mentioning
confidence: 99%